Brain structure and neurological and behavioural functioning in infants born preterm. (10th December 2018) - Kelly, Claire E; Thompson, Deanne K; Cheong, Jeanie LY; Chen, Jian; Olsen, Joy E; Eeles, Abbey L; Walsh, Jennifer M; Seal, Marc L; Anderson, Peter J; Doyle, Lex W; Spittle, Alicia J
Abstract : Aim: To examine: (1) relationships between brain structure, and concurrently assessed neurological and behavioural functioning, in infants born preterm at term‐equivalent age (TEA; approximately 38–44wks); and (2) whether brain structure–function relationships differ between infants born very (24–29wks) and moderate‐late (32–36wks) preterm. Method: A total of 257 infants (91 very preterm, 166 moderate‐late preterm; 120 males, 137 females) had structural magnetic resonance imaging (MRI) and neurological and behavioural assessments (Prechtl's general movements assessment, Neonatal Intensive Care Unit Network Neurobehavioral Scale [NNNS] and Hammersmith Neonatal Neurological Examination [HNNE]). Two hundred and sixty‐three infants (90 very preterm, 173 moderate‐late preterm; 131 males, 132 females) had diffusion MRI and assessments. Associations were investigated between assessment scores and global brain volumes using linear regressions, regional brain volumes using Voxel‐Based Morphometry, and white matter microstructure using Tract‐Based Spatial Statistics. Results: Suboptimal scores on some assessments were associated with lower fractional anisotropy and/or higher axial, radial, and mean diffusivities in some tracts: NNNS attention and reflexes, and HNNE total score and tone, were associated with the corpus callosum and optic radiation; NNNS quality of movement with the corona radiata; HNNE abnormal signs with several major tracts. Brain structure‐function associations generally did not differ between the very and moderate‐late preterm groups. Interpretation: White matter microstructural alterations may be associated with suboptimal neurological and behavioural performance in some domains at TEA in infants born preterm. Brain structure–function relationships are similar for infants born very preterm and moderate‐late preterm. What this paper adds: Brain volume is not related to neurological/behavioural function in infants born preterm at term. White matter microstructure is related to some neurological/behavioural domains at term. Brain–behaviour relationships are generally similar for infants born very preterm and moderate‐late preterm. What this paper adds: Brain volume is not related to neurological/behavioural function in infants born preterm at term. White matter microstructure is related to some neurological/behavioural domains at term. Brain–behaviour relationships are generally similar for infants born very preterm and moderate‐late preterm. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Resumen: Estructura cerebral y funcionamiento neurológico y conductual en lactantes prematuros: Objetivo: Examinar: (1) las relaciones entre la estructura del cerebro y el funcionamiento neurológico y conductual evaluado simultáneamente en bebés nacidos prematuros a la edad equivalente al término (EET; aproximadamente 38 a 44 semanas); (2) si las relaciones estructura‐función cerebral difieren entre los bebés nacidos muy prematuros (24–29 semanas) y prematuros‐moderados‐tardíos (32–36 semanas). Método: Un total de 257 bebés (91 muy prematuros, 166 prematuros moderados tardíos; 120 varones, 137 mujeres) tuvieron imágenes de resonancia magnética estructural (IRM) y evaluaciones neurológicas y conductuales (evaluación general de los movimientos de Prechtl, red de unidades de cuidados intensivos neonatales, escala neuroconductual [NNNS] y Hammersmith Neonatal Neurological Examination [HNNE]). Doscientos sesenta y tres bebés (90 muy prematuros, 173 moderados tardíos; 131 varones, 132 mujeres) se sometieron a RMN de difusión y evaluaciones. Se investigaron las asociaciones entre los puntajes de evaluación y los volúmenes cerebrales globales utilizando regresiones lineales, los volúmenes cerebrales regionales utilizando Morfometría Basada en Voxel y la microestructura de la materia blanca utilizando Estadísticas Espaciales Basadas en Tractos. Resultados: Las puntuaciones subóptimas en algunas evaluaciones se asociaron con una menor anisotropía fraccional y / o mayores difusividades axiales, radiales y medias en algunos tractos: la atención y los reflejos NNNS, y la puntuación total y el tono HNNE, se asociaron con el cuerpo calloso y la radiación óptica; Calidad de movimiento NNNS con la corona radiata; Signos anormales de HNNE con varios tractos importantes. Las asociaciones estructura‐función cerebral generalmente no difirieron entre los grupos prematuros muy moderados y tardíos. Interpretación: Las alteraciones microestructurales de la materia blanca pueden asociarse con un desempeño neurológico y de comportamiento subóptimo en algunos dominios neurológicos y conductuales en bebés nacidos prematuros evaluados a la EET. Las relaciones cerebro‐estructura‐comportamiento son similares para los bebés nacidos muy prematuros y para los prematuros moderados‐tardíos. Resumo: Estrutura cerebral e funcionamento neurológico e comportamental em lactentes nascidos prematuros: Objetivo: Examinar: (1) relações entre estrutura cerebral, e funcionamento neurológico e comportamental avaliados simultaneamente, em lactentes nascidos prematuros na idade equivalente ao termo (IET; aproximadamente 38‐44 semanas); 2) se a relação entre estrutura e função cerebral difere entre crianças nascidas muito prematuras (24–29sem) e moderadas‐tardias (32–36sem). Método: Um total de 257 lactentes (91 muito prematuros, 166 prematuros moderados‐tardios; 120 do sexo masculino, 137 do sexo feminino) tiveram imagens de ressonância magnética (IRM) e avaliações neurológicas e comportamentais (avaliação dos movimentos gerais de Prechtl, Escala Neurocomportamental da rede de Unidade de Cuidados Intensivos Neonatais [NNNS] e o Exame Neurológico Neonatal de Hammersmith [HNNE]). Duzentos e sessenta e três lactentes (90 muito prematuros, 173 prematuros moderados‐tardios; 131 do sexo masculino, 132 do sexo feminino) relizaram IRM por difusão e as demais avaliações. Associações foram investigadas entre os escores das avaliações e volumes cerebrais globais usando regressões lineares, volumens cerebrais regionais usando Morfometria baseada em voxels, e micro‐estrutura da substância branca usando Estatística especial baseada em tractos. Resultados: Escores subótimos em algumas avaliações foram associada scom menor anisotropia fractional e/ou maior difusividade axial, radial e média em alguns tractos: atenção e reflexos no NNNS, escore total e de tônus no HNNE, foram associados com o corpo caloso e radiação óptica; qualidade do movimento no NNNS com a coroa radiada; sinais anormais no HNNE com vários tractos importantes. Associações entre estrutura e função do cérebro geralmente não diferiram entre os grupos de prematuros muito prematuros e moderados‐tardios. Interpretação: Alterações da microestrutura da substância branca podem estar associadas a desempenho neurológico e comportamental subótimos em alguns domínios na IET em lactentes prematuros. Relações entre estrutura e função cerebral são similares para lactentes muito prematuros e moderados‐tardios.